Contribution of Self-Efficacy and Work Motivation in Shaping Caring Beharvior of Nurses - Hany Wihardja; Mey Lona Verawaty Zendrato; Ni Putu Ika Novita Gunawan; Rina Fitriani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Caring is the core of nursing practice, reflecting a nurse's approach to expressing genuine concern for the patient. Caring behavior of nurses is a form of caretaking that facilitates patients to achieve an optimal improvement in the quality of their recovery and health. Caring is driven by the self-confidence and work motivation of an individual nurse. This study aims to explore the correlation between nurses' self-efficacy, work motivation, and the caring behavior at Military Hospital in South Jakarta. This study used a cross-sectional design to explore the relationship between the variables of self-efficacy, motivation, and caring behavior. The study population included nursing staff from both inpatient and outpatient units. A total sample size was 122 nurses and was collected through a e-questionnaire and analyzed using descriptive statistics and bivariate correlation analysis. The results showed that there was a significant relationship between self-efficacy (p value 0.001, R = 0.295) and work motivation (p value 0.012, R = 0.236) with nurses' caring behavior. The correlation coefficient showed that both self-efficacy and work motivation had a positive correlation with nurses' caring behavior. Self-efficacy and work motivation significantly influence nurses’ caring behavior, highlighting the need for interventions to enhance these factors among nursing staff to improve patient care.